Legal Protection of Personal Data and Micro, Small, and Medium Enterprise (MSME) Data in the People's Business Credit Application Process - Gultom, Jeges Imanuelita; Debora, Debora; Sidauruk, Jinner (UNIVERSITAS PAKUAN, 2024)
A stable and growing economy is crucial for the advancement of a country, but unemployment remains a significant challenge faced by the government. To address this, the Indonesian government has promoted the development of MSMEs to create job opportunities and support the national economy. Since 2018, the People's Business Credit (KUR) program has been launched to support MSME financing through low-interest funding distributed by banks or financial institutions. This study discusses the legal protection of personal data and MSME data in the KUR application process, as well as the role of regulatory institutions such as the Financial Services Authority (OJK) and the Financial and Development Supervisory Agency (BPKP). The study's findings indicate that, despite the existence of Law No. 27 of 2022 on Personal Data Protection, the protection of MSME data remains suboptimal. More specific regulations are needed to ensure the security and confidentiality of data, thereby preventing misuse by irresponsible parties. In the implementation of KUR, OJK is responsible for maintaining the confidentiality of consumer financial data, while BPKP supervises the distribution of KUR funds through an integrated information system. Strengthening the roles of these institutions is vital to enhance accountability and the protection of MSME data, while also supporting the success of the KUR program in driving national economic growth.